2019
DOI: 10.3390/app9163342
|View full text |Cite
|
Sign up to set email alerts
|

Study of Annealing Temperature Effect on the Photovoltaic Performance of BiOI-Based Materials

Abstract: Bismuth oxyiodide (BiOI) is expected to be promising material for photovoltaic devices since it has good activity under the visible range. Here, we studied the annealing treatment on BiOI and its effect on the photovoltaic application. Firstly, the synthesized BiOI from Bi(NO3)3 and KI was annealed at varied temperatures (100–550 °C). The structural investigation by X-ray diffraction and Raman spectroscopy analysis was supported with morphology and optical analysis by scanning electron microscope (SEM) and UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
(79 reference statements)
2
23
0
Order By: Relevance
“…The XRD patterns confirm the achievement of the desired BiOI stoichiometry, with tetragonal phase (PDF# 10-0445). This phase has been already reported by several groups but using mainly Bi(NO 3 ) 3 as bismuth source [5,[14][15][16][17], [25][26][27][28][29][30][31][32], most of them by hydrothermal methods. Therefore, the same crystalline phase can be obtained regardless of the used precursor; in our case, bismuth acetate (BiAc) and subsalicylate (BiSs) by a simpler hydrothermal route.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The XRD patterns confirm the achievement of the desired BiOI stoichiometry, with tetragonal phase (PDF# 10-0445). This phase has been already reported by several groups but using mainly Bi(NO 3 ) 3 as bismuth source [5,[14][15][16][17], [25][26][27][28][29][30][31][32], most of them by hydrothermal methods. Therefore, the same crystalline phase can be obtained regardless of the used precursor; in our case, bismuth acetate (BiAc) and subsalicylate (BiSs) by a simpler hydrothermal route.…”
Section: Resultssupporting
confidence: 55%
“…However, a more likely explanation for these peaks is that they appear due to the energy supplied locally by the laser irradiation during the Raman measurement, providing enough energy to induce changes in the crystalline phase [38]. There is a report showing that BiOI is sensible to thermal processes, losing I-atoms while gaining O-atoms simultaneously, as temperature increases until it is transformed to β-Bi 2 O 3 [30]; even at lower temperatures [39]. This increase of temperature could be explained by a poor thermal conductivity of the BiOI powders.…”
Section: Resultsmentioning
confidence: 99%
“…We identified that our flaky structure is the same as the obtained morphology of prepared BiOI by other researchers. Flaky BiOI is considered as the basic shape of BiOI, and sometimes, it can be in the sheet-like material [15]. When the cycle reaction increases during the film preparation, it can result in the bigger flaky size of BiOI material which is shown by the lateral size of BiOI flake in (2) Bi 3+ + I − + H 2 O → BiOI + 2H + Fig.…”
Section: Surface Morphologymentioning
confidence: 99%
“…Furthermore, BiOI can be successfully synthesized by successive ionic adsorption and reaction with dip-coating (dip-SILAR) [5,[8][9][10], chemical bath deposition (CBD) [11], chemical vapor transport [2,12], mechanical grinding [13], and solvothermal reaction [6,14]. Conventional dip-SILAR, CBD, and slip-casting from BiOI powder [15] are also common to obtain the BiOI films for photovoltaic application.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike some metal oxide semiconductors composed of O 2p orbitals, the valence band of the Bi-based photocatalyst is formed by the hybridization of Bi 6s and O 2p orbitals [17,18]. The orbital hybridization reduces the forbidden bandwidth and disperses the valence band, thereby enhancing the visible light absorption capacity, making holes easy to move on the valence band, and hindering the recombination of photogenerated holes and photogenerated electrons [19][20][21]. BiOI has a narrow bandgap (1.7-1.9 eV), which can cover the entire visible light region, showing effective visible light photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%